Psychoanalysis as medicine, psychoanalysis as religion - Friedman, Richard A. (Journal of religion and health, 1995)
The author explores unfavorable comparisons between psychoanalysts and medical psychiatry, tracing the crisis in the mental health fields created by managed care. This current crisis is traced to an historical identification with the medical profession and a more recent dependence on third-party payments. He suggests reorganizing the profession as a religion or spiritual exercise as a way out of the crisis and as a way of revitalizing its practice.